O-GlcNAc transferase mediates O-GlcNAcylation of NLRP3 regulates pyroptosis in spinal cord injury - Zhichao Zeng; Xuqiang Liao; Xinjian Zhao (Brain Research Bulletin)
Background: Spinal cord injury (SCI) represents a severe disorder of the nervous system, imposing significant physical, psychological, and socioeconomic burdens on affected individuals and society. Objective: We investigated the implication of O-linked β-N-acetylglucosamine (O-GlcNAcylation) in regulating pyroptosis related proteins at the posttranslational level. Materials and methods: PC12 cells were stimulated with lipopolysaccharide (LPS). The O-GlcNAcylation pathway was modified by manipulating the expression of O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA). Pro-inflammatory cytokine levels and cell pyroptosis were assessed. Co-immunoprecipitation (Co-IP) assays were employed to investigate the interaction between NLRP3 and OGT. For in vivo studies, an established SCI rat model was utilized. Levels of pro-inflammatory factors, NLRP3 inflammasome components, and proteins associated with pyroptosis were measured. Results: Both O-GlcNAc levels and OGT expression were significantly elevated in the SCI model cells. Inhibition of OGT led to a marked reduction in the levels of pro-inflammatory cytokines and a suppression of pyroptosis. Furthermore, inhibition of OGT resulted in downregulation of NLRP3 and its O-GlcNAcylation, while overexpression of OGT produced the opposite effect. We verified the endogenous and exogenous interactions between NLRP3 and OGT. Importantly, knockout of OGT mitigated the progression of SCI in an animal model, suggesting a protective role of OGT inhibition in SCI. Discussion and conclusion: This study preliminarily proved that the mechanism of OGT mediated O-GlcNAcylation of NLRP3 participates in the action of pyroptosis in SCI. Targeting OGT and NLRP3 may be novel therapy method in SCI.